P2Y6 Receptor Activation Aggravates NLRP3-dependent Microglial Pyroptosis via Downregulation of the PI3K/AKT Pathway in a Mouse Model of Intracerebral Hemorrhage - Li, Yulong; Tu, Huiru; Zhang, Shengfan; Ding, Zhiquan; Wu, Guiwei; Piao, Jifeng; Lv, Dingyi; Hu, Libin; Li, Feng; Wang, Qinghua (Molecular neurobiology, 2024)
Pro-inflammatory signals generated after intracerebral hemorrhage (ICH) trigger a form of regulated cell death known as pyroptosis in microglia. White matter injury (WMI) refers to the condition where the white matter area of the brain suffers from mechanical, ischemic, metabolic, or inflammatory damage. Although the p2Y purinoceptor 6 (P2Y6R) plays a significant role in the control of inflammatory reactions in central nervous system diseases, its roles in the development of microglial pyroptosis and WMI following ICH remain unclear. In this study, we sought to clarify the role of P2Y6R in microglial pyroptosis and WMI by using an experimental mouse model of ICH. Type IV collagenase was injected into male C57BL/6 mice to induce ICH. Mice were then treated with MRS2578 and LY294002 to inhibit P2Y6R and phosphatidylinositol 3-kinase (PI3K), respectively. Bio-conductivity analysis was performed to examine PI3K/AKT pathway involvement in microglial pyroptosis. Quantitative Real-Time PCR, immunofluorescence staining, and western blot were conducted to examine microglial pyroptosis and WMI following ICH. A modified Garcia test, corner turning test, and forelimb placement test were used to assess neurobehavior. Hematoxylin-eosin staining (HE) was performed to detect cells damage around hematoma. Increases in the expression of P2Y6R, NLRP3, ASC, Caspase-1, and GSDMD were observed after ICH. P2Y6R was only expressed on microglia. MRS2578, a specific inhibitor of P2Y6R, attenuated short-term neurobehavioral deficits, brain edema and hematoma volume while improving both microglial pyroptosis and WMI. These changes were accompanied by decreases in pyroptosis-related proteins and pro-inflammatory cytokines both in vivo and vitro. Bioinformatic analysis revealed an association between the PI3K/AKT pathway and P2Y6R-mediated microglial pyroptosis. The effects of MRS2578 were partially reversed by treatment with LY294002, a specific PI3K inhibitor. P2Y6R inhibition alleviates microglial pyroptosis and WMI and ameliorates neurological deficits through the PI3K/AKT pathway after ICH. Consequently, targeting P2Y6R might be a promising approach for ICH treatment.